A low profile antipodal Vivaldi antenna with improved front‐to‐back ratio and sidelobe levels for 5G applications. Issue 9 (16th June 2022) - Dixit, Amruta S.; Kumar, Sumit
Abstract: In this article, a novel miniaturized antipodal Vivaldi antenna (AVA) is proposed with significant improvement in the back and sidelobe levels (SLLs) to mitigate their adverse effect on the communication system components. The proposed AVA enhances SLL up to −5.7 dB and front to back ratio (FBR) to 20.2 dB. These improvements are accomplished by antenna size reduction and gain enhancement. The proposed AVA is miniaturized by 22.27% and the gain is increased up to 4 dBi compared to the conventional AVA (CAVA). The AVA is designed by incorporating substrate integrated waveguide (SIW) and corrugations. The use of corrugations improves the FBR and gain. Next, the improvements in the bandwidth and SLL are achieved by SIW. The antenna dimensions are 15 × 6 × 0.5 mm 3 and it provides the enhanced and almost constant gain of 9.5 ± 1.5 dBi. The antenna is designed for the 38 GHz band of 5G applications and it has an impedance bandwidth of 36–48.43 GHz. The efficiency of an antenna is above 94% over the desired frequency range. The antenna is fabricated and verified with experimental results. The proposed antenna makes it as one of the best choices as a 5G antenna.